The role of pharmacists in crisis management and humanitarian missions: current state and perspectives - Pavlović, Nebojša (PONS - medicinski časopis, 2021)
According to the World Disasters Report from 2018, 3,751 natural disasters occurred in previous ten years, which affected 2 billion people, and according to the United Nations report, 134 million people required help. COVID-19 pandemic revealed the unpreparedness of humanity for the global catastrophe, and in the first six months of the pandemic, 50 million people faced the consequences of more than a hundred disasters classified as catastrophes. We aimed to determine which competencies of pharmacists are necessary for performing activities in humanitarian missions and crisis situations, as well as to analyze existing and possible options of pharmacists’ involvement in the healthcare team, as well as pharmacists’ contribution to the healthcare system in crisis situations. In crisis situations, the pharmacist, in addition to traditional, performs a wide range of non-traditional activities, manages the system of drug and medical device supply, participates in providing emergency medical care, patient care, supervision of therapy, immunization, but also in establishing crisis management policy and implementing adopted principles. The involvement of pharmacists in humanitarian work is still insufficient, although progress has been made, while the COVID-19 pandemic has certainly opened a new chapter in the development of pharmaceutical profession, which will certainly significantly change after the current crisis, along with other professions. Active involvement of pharmacists in healthcare teams is necessary in order to optimally use their expertise, and they themselves to gain experience, which would enable the formation of good practice standards in future and improving the outcomes of humanitarian or public health missions.
Keywords: pharmacist; humanitarian work; pandemic; pharmaceutical services; pharmacy practice